Efektivitas Layanan Bimbingan Klasikal Dengan Teknik PJBL Untuk Meningkatkan Pemahaman Pilihan Karir Siswa Tunarungu Kelas IX - Riska Nur Anisa (Publikasi Indonesia, 2022)
The role of professional teachers in the learning process is very important as the key to student learning success. Professional teachers are teachers who are competent to build a good learning process so that they can produce quality education and excellent character. This makes the teacher a component that is the focus of the attention of the Government and local governments in improving the quality of education, especially regarding teacher competence. The design in this study uses Counseling Guidance Action Research (PTBK), the implementation of which includes four steps (steps): (1) action planning; (2) implementation of actions; (3) Observation; (4) reflection. Researchers first carefully plan the type of action to be performed. Then carry out activities on the planned actions. Next, the researcher observes the process of implementing the action and the consequences it causes. Finally, the researcher then reflects on the actions that have been taken. This research results in classes becoming more lively and colorful because they are student-centered and make students' reflection material to strengthen and direct follow-up plans in the learning process.